Systemic lupus erythematosus complicated with macrophage activation syndrome mimicking COVID-19 multisystemic inflammatory syndrome in children - Jesús Domínguez-Rojas; Noé Atamari-Anahui; Kenny Chonlon-Murillo; Mariela Tello; Álvaro Coronado-Muñoz (Permanyer, 2021)
Background: Macrophage activation syndrome (MAS) is characterized by excessive activation of macrophages and lymphocytes, leading to multiorgan dysfunction. As the initial manifestation of systemic lupus erythematosus (SLE), MAS is rare in children. Due to the COVID-19 pandemic, it is vital to identify the MAS as it shares similar characteristics with the multisystem inflammatory syndrome in children (MIS-C). Case report: We report the case of an 11-year-old male adolescent with symptoms of MIS-C. Although with negative results of RT-PCR (reverse transcription-polymerase chain reaction) and serology for SARS-CoV-2, contact with a positive COVID-19 relative was reported. When admitted to a referral hospital center, the patient received standard treatment for MIS-C. Although the same scheme was given on three occasions, the patient showed no response to initial therapy. Thus, the patient was classified as a refractory case. When the study was extended to other differential diagnoses, we found MAS associated with SLE. Therefore, the patient was treated with etoposide, cyclosporine, dexamethasone, and methotrexate and showed a good clinical response. Conclusions: MAS associated with SLE is rare in the pediatric population. MAS shares inflammatory markers with the MIS-C and is often confused with rheumatologic, infectious, and neoplastic entities. Reporting this case is important to identify differential diagnoses in patients presenting as MIS-C and decide on timely treatment, as it could be harmful or even fatal if a definitive diagnosis is not obtained on time.